Effect of mesoporous SBA-15 silica on the thermal stability of isotactic polypropylene based nanocomposites prepared by melt extrusion. (August 2018) - Barranco-García, R.; Cerrada, M.L.; Ressia, J.A.; Vallés, E.M.; García-Peñas, A.; Pérez, E.; Gómez-Elvira, J.M.
Abstract: The influence of mesoporous SBA-15 on the thermal stability of nanocomposites with isotactic polypropylene has been evaluated in detail, both under inert and air conditions, by performing dynamic weight loss measurements and by tracking the evolution of degradation species in materials prepared by melt extrusion. A superior thermal stability has been found in the composites, both under nitrogen and air, compared with that observed in the pristine PP. An almost identical effect has been found under those two atmospheres, in spite that the mechanisms involved in both of them are completely different. The rheological characteristics of these materials turn out the driving aspect in the observed thermal behaviour, prevailing on other specific detrimental parameters. Highlights: Basic aspects of the thermal stability of PP/SBA-15 nanocomposites obtained by melt compounding are studied. Among the factors involved in polyolefins' stability, rheological features of these materials are the driving aspect. This work shows that mesoporous SBA-15 has a great potential in the production of PP improved based nanocomposites.